Trifunctional Epoxy Resin Composites Modified by Soluble Electrospun Veils: Effect on the Viscoelastic and Morphological Properties - Ognibene, Giulia (Materials (Basel), 2018)
Electrospun veils from copolyethersulfones (coPES) were prepared as soluble interlaminar veils for carbon fiber/epoxy composites. Neat, resin samples were impregnated into coPES veils with unmodified resin, while dry carbon fabrics were covered with electrospun veils and then infused with the unmodified epoxy resin to prepare reinforced laminates. The thermoplastic content varied from 10 wt% to 20 wt%. TGAP epoxy monomer showed improved and fast dissolution for all the temperatures tested. The unreinforced samples were cured first at 180 °C for 2 h and then were post-cured at 220 °C for 3 h. These sample showed a high dependence on the curing cycle. Carbon reinforced samples showed significant differences compared to the neat resin samples in terms of both viscoelastic and morphological properties.